Dermatology secrets plus - Fitzpatrick, James E. 1948-; Morelli, Joseph G. (Secrets series, 2016)
For 30 years, the highly regarded Secrets Series® has provided students and practitioners in all areas of health care with concise, focused, and engaging resources for quick reference and exam review. Dermatology Secrets Plus, 5th Edition, by Drs. James E. Fitzpatrick and Joseph G. Morelli, features the Secrets' popular question-and-answer format that also includes lists, tables, and an informal tone - making reference and review quick, easy, and enjoyable